The Effect of Profitability and Leverage on Firm Value with Dividend Policy as an Intervening Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2021–2024 - Pransiskus Sitinjak; Sarida Sirait; Eko Deswin M. Siringo-Ringo (CV. ADMITECH SOLUTIONS, 2026)
This research aims to determine how profitability and leverage affect firm value with dividend policy as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. Firm value is a crucial indicator for assessing business performance and sustainability, while profitability and leverage are key factors that can influence investment decisions and profit distribution. Dividend policy, in itself, acts as a signal to investors regarding the company's financial condition. This study uses the multiple linear regression method with data obtained through the companies' annual reports on the IDX. Profitability is measured using Return On Assets (ROA), Leverage is measured by the Debt to Equity Ratio (DER), Firm Value is measured by the Price to Book Value (PBV), and Dividend Policy is measured by the Dividend Payout Ratio (DPR). The results of this study indicate that profitability and leverage have a significant effect on firm value. However, leverage does not have a significant effect on dividend policy, and dividend policy cannot mediate the leverage variable's effect on firm value.